T cell receptor-driven transendothelial migration of human effector memory CD4 T cells involves Vav, Rac and Myosin IIA - Manes, Thomas D. (2013)
Human effector memory (EM) CD4 T cells may be recruited from the blood into a site of inflammation in response either to inflammatory chemokines displayed on or specific antigen presented by venular endothelial cells (ECs), designated as chemokine-driven or TCR-driven transendothelial migration (TEM), respectively. We have previously described differences in the morphological appearance of transmigrating T cells as well as in the molecules that mediate T cell-EC interactions distinguishing these two pathways. Here we report that TCR-driven TEM requires ZAP-70-dependent activation of a pathway involving Vav, Rac and myosin IIA. Chemokine-driven TEM also utilizes ZAP-70, albeit in a quantitatively and spatially different manner of activation, and is independent of Vav, Rac and mysosin IIA, depending instead on an as yet unidentified GTP exchange factor that activates Cdc42. The differential use of small Rho family GTPases to activate the cytoskeleton is consistent with the morphological differences observed in T cells that undergo TEM in response to these distinct recruitment signals.